Use of high dose cyproterone acetate and risk of intracranial meningioma in women: cohort study. (3rd February 2021) - Weill, Alain; Nguyen, Pierre; Labidi, Moujahed; Cadier, Benjamin; Passeri, Thibault; Duranteau, Lise; Bernat, Anne-Laure; Yoldjian, Isabelle; Fontanel, Sylvie; Froelich, Sébastien; Coste, Joël
Abstract: Objective: To assess the risk of meningioma associated with use of high dose cyproterone acetate, a progestogen indicated for clinical hyperandrogenism. Design: Observational cohort study. Setting: Data from SNDS, the French administrative healthcare database, between 2007 and 2015. Participants: 253 777 girls and women aged 7-70 years living in France who started cyproterone acetate between 2007 and 2014. Participants had at least one reimbursement for high dose cyproterone acetate and no history of meningioma or benign brain tumour, or long term disease status. Participants were considered to be exposed when they had received a cumulative dose of at least 3 g during the first six months (139 222 participants) and very slightly exposed (control group) when they had received a cumulative dose of less than 3 g (114 555 participants). 10 876 transgender participants (male to female) were included in an additional analysis. Main outcome measure: Surgery (resection or decompression) or radiotherapy for one or more intracranial meningiomas. Results: Overall, 69 meningiomas in the exposed group (during 289 544 person years of follow-up) and 20 meningiomas in the control group (during 439 949 person years of follow-up) were treated by surgery or radiotherapy. The incidence of meningioma in the two groups was 23.8 and 4.5 per 100 000 person years, respectively (crude relative risk 5.2, 95% confidence interval 3.2 to 8.6; adjusted hazard ratio 6.6, 95% confidence interval 4.0 to 11.1). The adjusted hazard ratio for a cumulative dose of cyproterone acetate of more than 60 g was 21.7 (10.8 to 43.5). After discontinuation of cyproterone acetate for one year, the risk of meningioma in the exposed group was 1.8-fold higher (1.0 to 3.2) than in the control group. In a complementary analysis, 463 women with meningioma were observed among 123 997 already using cyproterone acetate in 2006 (risk of 383 per 100 000 person years in the group with the highest exposure in terms of cumulative dose). Meningiomas located in the anterior skull base and middle skull base, particularly the medial third of the middle skull base, involving the spheno-orbital region, appeared to be specific to cyproterone acetate. An additional analysis of transgender participants showed a high risk of meningioma (three per 14 460 person years; 20.7 per 100 000 person years). Conclusions: A strong dose-effect relation was observed between use of cyproterone acetate and risk of intracranial meningiomas. A noticeable reduction in risk was observed after discontinuation of treatment.